Lactating adenoma arising from a tubular adenoma in a pediatric patient - Maria Tran; Roshini Pudhucode; Janice Aportela; Smita Sharma; Marie Crandall; Bharti Jasra (Elsevier, 2019)
We are reporting a rare case of tubular adenoma of the breast in a pediatric patient progressing to a lactating adenoma during pregnancy. The patient first noticed the mass at 14 years of age, and the size did not change considerably until pregnancy. The patient became pregnant at 16 years of age, and the breast tumor size increased to 20 x 20 cm in size. Magnetic Resonance Imaging (MRI) revealed an enhancing right breast mass. Initial ultrasonography (US) showed a large, complex, mixed cystic and solid mass with microlobulated margins. A follow-up US a year later depicted significantly increased heterogenous mass size. Initial US-core needle biopsy revealed a single layer of epithelial cells with variable stoma and chronic inflammation. A lactating adenoma was declared on repeat US core needle biopsy. No calcifications were noted, but due to overwhelming size, the patient was carefully monitored through pregnancy and post-partum. After delivery, the mass gradually decreased in size over the course of a year to 6 x 5 cm. : A tubular adenoma of the breast was found in a 14-year-old patient progressing to a lactating adenoma during her pregnancy at 16 years of age. The lactating adenoma grew to 20 x 20 cm in size during the second and third trimester. Further testing revealed no malignancy. The tumor significantly regressed in size postpartum. Keywords: Tubular adenoma, Lactating adenoma